Alarming carcinogenic and non-carcinogenic risk of heavy metals in Sabalan dam reservoir, Northwest of Iran. Issue 1 (1st January 2021) - Aradpour, Saber; Noori, Roohollah; Vesali Naseh, Mohammad Reza; Hosseinzadeh, Majid; Safavi, Salman; Ghahraman-Rozegar, Fardin; Maghrebi, Mohsen
ABSTRACT: This research aims to assess contamination status of water and sediment in Sabalan dam reservoir (SDR) and evaluate the impact of water withdrawal depths on the carcinogenic and non-carcinogenic risks of metals for exposed people. Results of metal pollution indices revealed some degree of pollution in water and sediment of the reservoir, especially associated with arsenic. Risk assessment of metals in water of the SDR for non-carcinogenic materials through different scenarios of water withdrawal depth revealed that consuming water from the depth of 10 m can be somewhat troublesome to human health. The carcinogenic risk of arsenic from depth of 10 m of the reservoir was about four times greater than that from water surface. Minimum carcinogenic risk of consuming water in the reservoir was found to be 1.69 × 10E-4, which is higher than the maximum limit proposed by the U.S. EPA, indicating the water consumption from the SDR can result in harmful effects on human health.